Phlogacanthus geoffrayi Benoist (Acanthaceae): A New Record to the Flora of Vietnam - Hai, Do Van; Hoan, Duong Thi; Choudhary, Ritesh Kumar (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 2, 2020)
Phlogacanthus geoffrayi is reported here as a newly recorded species from Vietnam. This species is morphologically allied to Phlogacanthus turgidus but differs in having a significantly bigger calyx and staminodes. The specimens were collected from Song Cau district of Phu Yen province. Description, line-drawing, photographs, and notes on ecology and distribution are provided.